Answer:
(a) -6
Step-by-step explanation:
P(x) = ax^3 +bx - 3
- P(-1) = -a-b-3 = 0
- therefore a+b=-3
- P(1) = a+b-3
- P(1) = -3 - 3 = -6
- (a)
Answer:
1/6
Step-by-step explanation:
Negative one half power is the reciprocal of the square root, 1/6
9514 1404 393
Answer:
3
Step-by-step explanation:
For f(x) = x^3 -2x^2 -7x +5 and x=1/(2-√3), we have ...
f(x) = ((x -2)x -7)x +5
and ...
x = 1/(2-√3) = (2+√3)/(2^2 -3) = 2+√3
Then ...
f(2+√3) = ((2 +√3 -2)(2 +√3) -7)(2 +√3) +5
= (3+2√3 -7)(2+√3) +5
= 2(√3 -2)(√3 +2) +5 = 2(3 -4) +5 = -2 +5
f(1/(2 -√3)) = 3
_____
If you really mean x = (1/2) -√3, then f(x) = (42√3 -3)/8.
Answer:
Brainly's honor code doesn't allow quiz questions to be posted.
"Students are never allowed 2 post questions directly from tests, quizzes, and assessments, or copy answers found on Brainly during tests, quizzes, and assessments."